On-Off Water Level Control and IoT Monitoring for Aquaponics Systems - Fadil, Muhammad; Ahmad Munir; Muhammad Tahir Sapsal (Salaga Journal, 2023)
Aquaponic system is a cultivation method that combines fish and plant farming or aquaculture and hydroponics that are mutually beneficial (symbiotic mutualism) at one time. Aquaponic water level control to maintain water volume is still done using conventional methods. Therefore, this research aims to produce a good control system to control aquaponic water levels equipped with an on/off control system and can monitor water levels remotely. This research method includes designing a control system for water level, functional test and performance test of the control system to aquaponics as well as data loss test and network delay to Thinger.io platform. The parameter observed was the water level. The results showed that the on/off control system was able to regulate the water level with no overshoot, the settling time reached for a height of 20 cm was 9 minutes, a height of 25 cm for 22 minutes and for a height of 30 cm for 34 minutes and the steady state error that occurred was still within the tolerance limit. The IoT system using the Thinger.io platform implemented is able to send data and store data during the testing process, and the Thinger.io platform can monitor water levels remotely and provide data in excel format. The test results of lost data with an average of 1.81% and delay testing with an average of 0.88%, based on data mapped every 6 hours, the largest percentage of lost data and delay occurs at 00.00 -06.00 GMT +8.